A Case Study on Distribution of Gemstone in Bela Ophiolite, District Khuzdar, Balochistan - Khan, Salman; Ghaffar, Abdul; Ullah, Inayat; Murad, Fida; Ahmed, Jalil; Kakar, Muhammad Ishaq (International Journal of Economic and Environmental Geology, 2023)
Bela Ophiolite and suture zone host several types of gemstones in the underlain and overlain rocks such as garnet (demantoid and almandine), quartz, brucite, malachite, chrysocolla, azurite, calcite, natrolite, green chert, jasper, serpentine, agate, epidote, augite and prehnite. However, the rare gemstones including demantoid garnet are found as dodecahedron green crystals associated with the altered peridotite rocks such as serpentinite. Brucite is found in the botryoidal habit in the ultramafic rocks of Bela Ophiolite associated with the chromite mines in the Baran Lak and Amorzai area of Wadh in the host rock dunite. The serpentine is found in several locations associated with the altered ultramafic rocks formed after the serpentinization of peridotite. Furthermore, one of the rare gemstones such as petroleum and diamond quartz is formed due to the hydrothermal intrusion in the sedimentary rocks such as limestone; calcite also occurs in limestone as dogtooth crystals. While azurite, malachite and chrysocolla are formed as secondary deposits in the oxidized zone of copper and sulphide mines in the Manjawi, Nal and Sonaro associated adjacent to basalt. Moreover, epidote is found as green crystals having porphyritic texture in the host rock granite mainly in the Bakhalo area, Wadh. Agate, jasper, green chert and several other kinds of chert are found associated with the basalt chert unit in the mélange and gossan. In addition to that natrolite is found in the Nal ophiolite mainly in the Hazarghanji town found associated with the cracks and vugs of dolerite dykes as fibrous and cylindrical crystals. In metamorphic sole rocks of Bela Ophiolite in the Sonaro area, marble and quartzite are associated with the metamorphic rocks such as greenschist and amphibolite facies that are formed during the e volution period of the ophiolite. In pegmatite gabbro, the elongated and prismatic black crystals of augite are found in the host rock gabbro near the Ornach cross area, and the prehnite gemstone is found associated with the basalt and gabbroic rocks transition zone in the Ornach area.